An optimisation strategy for concurrent Supply Chain Finance schemes. Issue 2 (March 2019) - Gelsomino, Luca Mattia; de Boer, Ronald; Steeman, Michiel; Perego, Alessandro
Abstract: The uncertainty and financial instability that has plagued companies and industries in the last decade is one of the root causes behind the development of Supply Chain Finance (SCF), a set of schemes aiming to optimise the management of financial flows at the supply chain level. Recent years have seen a proliferation of different SCF schemes, with different impacts on working capital costs and requirements throughout the supply chain. The practicality of SCF usage indicates that the concurrent adoption of multiple schemes is not only possible, but even likely. However, literature on SCF still focuses on individual SCF schemes, while the concurrent adoption of multiple SCF schemes remains largely unaddressed. Thus, the objective of this paper is to assess the tangible benefits deriving from a multi-scheme SCF strategy. Based on the analytical formulation of the benefits of three relevant SCF schemes (Reverse Factoring, Inventory Financing and Dynamic Discounting), the paper formalises a model that investigates the benefits that a buyer can achieve by onboarding suppliers onto these three schemes. The results show how working capital requirements and the cost of finance represent the key parameters to assessing the benefits of the concurrent adoption of multiple SCF schemes. Moreover, the funding limits of the SCF schemes themselves strongly affect the relevance of such strategies; strict limits will increase the relevance of having 'alternative' schemes available to onboard suppliers. To highlight the managerial relevance of the model, the article provides a numerical example based on a real-world application. Highlights: Concurrent adoption of multiple Supply Chain Finance schemes is becoming common among practitioners. Concurrent adoption of multiple SCF scheme has potential to lead to higher overall tangible benefits for the adopting buyer. Parameters affecting such benefits are working capital costs and requirements within the supply base, as well as scheme-dependent funding limits.